2020
DOI: 10.1002/path.5503
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of chitinase‐3‐like protein 1 is associated with structural recurrence in patients with differentiated thyroid cancer

Abstract: We previously identified that the expression of chitinase‐3‐like protein 1 (CHI3L1) was upregulated during thyroid cancer progression. Here, we investigated the prognostic significance of CHI3L1 expression in thyroid neoplasms and examined the potential oncogenic roles. CHI3L1 immunochemical staining was performed on tissue microarrays of benign and malignant thyroid tumours. Compared with normal thyroid tissue and benign thyroid lesions that had low or no detectable CHI3L1 expression, CHI3L1 was overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…A high expression of NPC2 and its significant elevation in PTC were also detected in meta-analyses of public PTC transcriptomes [28]. Overexpression of CHI3L1, the most up-regulated gene in the analyzed PTC, was reported as associated with metastatic PTC [29] and its recurrence [30]. Significantly decreased expression of TFF3, the most down-regulated gene in our study, was also reported in several other studies (e.g., [31]).…”
supporting
confidence: 87%
“…A high expression of NPC2 and its significant elevation in PTC were also detected in meta-analyses of public PTC transcriptomes [28]. Overexpression of CHI3L1, the most up-regulated gene in the analyzed PTC, was reported as associated with metastatic PTC [29] and its recurrence [30]. Significantly decreased expression of TFF3, the most down-regulated gene in our study, was also reported in several other studies (e.g., [31]).…”
supporting
confidence: 87%
“…High expression of NPC2 and its significant elevation in PTC were also detected in meta-analyses of public PTC transcriptomes [20]. Overexpression of CHI3L1, the most up-regulated gene in the analyzed PTC, was reported as associated with metastatic PTC [21] and its recurrence [22]. Significantly decreased expression of TFF3, the most down-regulated gene in our study, was also reported in several other studies (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Several lines of evidence have reported the pivotal role of anoikis resistance in lymphatic metastasis of cancer ( 10 , 11 ), even in lymphatic metastasis of thyroid cancer ( 18 20 ). Furthermore, anoikis resistance was reported to be significantly correlated with positive lymph node metastasis in various cancers ( 12 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…In several cancer scenario, anoikis resistance correlated significantly with positive lymph node metastasis status, including esophageal carcinoma ( 12 , 13 ), melanoma ( 14 ), tongue cancer ( 15 ), breast cancer ( 16 ), and colorectal cancer ( 17 ). Importantly, development of anoikis resistance has been reported to significantly contribute to lymphatic metastasis of thyroid cancer ( 18 20 ). Therefore, investigating the underlying mechanism of anoikis resistance in lymphatic metastasis of thyroid cancer is of great necessity.…”
Section: Introductionmentioning
confidence: 99%